PENGARUH IKLIM ORGANISASI DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PADA DEALER MOBIL TOYOTA (Studi Pada Karyawan Bagian Kantor PT.Agung Automall Cabang Arengka Pekanbaru) - Armita, Elga; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine how much influence organizational climate and career development on the performance of employees in the office. Sampels in this study were taken as many as 50 respondens and techniques used census. The data in this study using survey method through questionnares filled by office employee. Data were obtained by using simple regression analysis and multiple regression analysis. The result of this study show that organizational climate has a significant impact on performance of employees in the office. Career development has a significant impact on performance of employees in the office. And then simultaneously organizational climate and career development have a significant impact on performance of employees in the office. Subsequent research is suggested to use other methods in researcing employee’s performance, for example through in-depth interviews of respondents.Keywords: Organizational Climate,Career Development, And Employee’s Performance